(untitled) (Cuidado y Ocupación Humana, 2024)
This clinical case presents a patient diagnosed with malignant stomach tumor and multiple comorbidities, including hypertension, diabetes mellitus, irritable bowel syndrome, hypothyroidism, and digestive hemorrhage, which significantly affected the digestive system and overall quality of life. The occupational therapy intervention began with a comprehensive assessment and the use of standardized evaluation formats, allowing the identification of needs, interests, and residual capacities. Based on this, follow-up plans and purposeful activities were designed to enhance occupational performance, promoting improvements in motor skills, processing abilities, sensory functions, and neuromusculoskeletal functions, with the goal of increasing independence in activities of daily living. The results demonstrated progress not only in functional performance but also in the patient’s emotional well-being and motivation, achieved through a personalized, occupation-centered approach with active participation. Family support, especially from the patient’s children, played a crucial role in implementing self-care strategies at home, strengthening continuity of the therapeutic process. In conclusion, this case highlights the importance of interdisciplinary collaboration and purposeful activities in oncological rehabilitation, underscoring the impact of occupational therapy on functionality, autonomy, and overall quality of life. The findings reinforce occupational therapy as a holistic and individualized intervention capable of addressing both physical and emotional dimensions, thereby supporting recovery and meaningful participation in patients with cancer